Development of a 1kw Prototype Kerosene-Powered Vapour Absorption Refrigerator for Domestic Refrigeration Applications - Amosun, Taiwo Semiu; Omoniyi Kaffo, Paul (Borobudur Engineering Review, 2023)
Vapour absorption is an attractive method of utilizing low grade energy directly for cooling. This work attempts to develop a kerosene-powered vapour absorption refrigerator for domestic refrigeration applications. It is designed to comprise five major components: evaporator, absorber, generator, pump and condenser and their capacities were determined to be 80W, 350W, 180W, 20W and 90W respectively. The refrigerator is a medium-size one and is designed for domestic purposes only. It uses ammonia and water as primary and secondary working fluids. Parts were designed, fabricated and assembled accordingly. Finally, the performance test was carried out and the refrigerator was able to achieve an evaporative temperature of 7oC and had actual coefficient of performance (COP) of 0.16. It also takes 35 minutes to cool 1litre of water at ambient temperature to 0oC. The operating temperature of the refrigerator is between 7oC to 43oC. General energy equation of the refrigerator gave 875.237KJ.